Good parks – bad parks: the influence of perceptions of location on WTP and preference motives for urban parks. Issue 2 (3rd April 2017) - Andrews, Barnaby; Ferrini, Silvia; Bateman, Ian
ABSTRACT: Urban parks generate substantial public benefits, yet explicit economic assessments of such values remain relatively rare. Surveys of willingness to pay (WTP) were undertaken to assess such values for proposed new parks. The analysis assessed how preference motives and values varied according to the location of parks. Results revealed greater altruistic motivation and higher overall values for the creation of inner city as opposed to suburban parks. Spatial decomposition revealed that, after controlling for other determinants such as incomes, values generally increase for households closer to proposed parks, but that a significant downturn in values is evident for households located very close to a proposed inner city park; a finding which echoes concerns regarding the potential for such sites to provide a focus for antisocial behaviour. While these findings provide strong overall support for provision of public parks they highlight, the importance of perceptions of location and the potential for localised dis-benefits.